Muckenhoupt–Wheeden theorem for generalized f-Riesz-type potentials - Knopova, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
The Muckenhoupt–Wheeden theorem is proved for one class of potentials. As a consequence, we describe the equivalent norm in the space of generalized Bessel potentials of negative order.